Facial fracture repair and diabetes mellitus: An examination of postoperative complications. (23rd September 2016) - Raikundalia, Milap; Svider, Peter F.; Hanba, Curtis; Folbe, Adam J.; Shkoukani, Mahdi A.; Baredes, Soly; Eloy, Jean Anderson
Abstract : Objectives/Hypothesis: Our objectives included using a nationally representative resource to evaluate charges, demographics, and complication rates among diabetics undergoing surgical repair of facial fractures. Methods: We evaluated the Nationwide Inpatient Sample, a database encompassing nearly 8 million hospitalizations, for patients with a diagnosis of a facial fracture who underwent surgical intervention during their hospitalization. Patients were organized by whether they had a diagnosis of diabetes mellitus (DM). Results: Of 45, 509 inpatients included, diabetics had greater costs, longer length of stays, and were significantly more likely to have a host of baseline comorbidities. On multivariate logistic regression corrected for age, race, gender, and preexisting cardiac disease, DM patients had significantly greater odds for cardiac complications (3.3; P < 0.001) and hepatic failure (15.0; P = 0.007). There were no significant differences associated with DM in the rates of enophthalmos, epiphora, and diplopia among patients with orbital fractures. Diabetics did have a significantly greater risk of postoperative infection after mandible repair. Conclusion: In addition to a significant association with greater length of stay and increased hospital charges, DM patients undergoing surgical repair of facial fractures had a significantly greater risk of postoperative complications, including cardiac complications. Diabetics undergoing mandible repair had a greater risk of postoperative infection, even upon controlling for demographic factors, suggesting the need for further study evaluating the role of postoperative antibiotic prophylaxis in this patient population. These findings reveal the potential value of developing and using standardized postoperative care algorithms aimed at minimizing complications in this susceptible population. Level of Evidence: 2c. Laryngoscope, 127:809–814, 2017